2020
DOI: 10.5009/gnl19035
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo T Cell Cytokine Expression Predicts Survival in Patients with Severe Alcoholic Hepatitis

Abstract: Alcoholic hepatitis (AH) is an acute inflammatory liver condition with high early mortality rate. Steroids improve shortterm survival but nonresponders have the worst outcomes. There is a clinical need to identify these high-risk individuals at the time of presentation. T cells are implicated in AH and steroid responsiveness. We measured ex vivo T cell cytokine expression as a candidate biomarker of outcomes in patients with AH. Consecutive patients (bilirubin >80 µmol/L and ratio of aspartate aminotransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…However, these studies did not examine the relationship between IL‐10 and infection in AH patients. In contrast to the current study, a T‐cell cytokine release assay predicted survival in AH patients, with increased production of anti‐inflammatory interleukin (IL)‐10 associated with death 24 . Another study found that polymorphisms in genes resulting in high TNF‐α and low IL‐10 production were associated with higher rates of sepsis in patients with AH 25 .…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…However, these studies did not examine the relationship between IL‐10 and infection in AH patients. In contrast to the current study, a T‐cell cytokine release assay predicted survival in AH patients, with increased production of anti‐inflammatory interleukin (IL)‐10 associated with death 24 . Another study found that polymorphisms in genes resulting in high TNF‐α and low IL‐10 production were associated with higher rates of sepsis in patients with AH 25 .…”
Section: Discussioncontrasting
confidence: 89%
“…Levels of IFN‐γ were found to be reduced in the serum of patients with chronic ARLD 30 . In a cytokine release assay, levels of T‐cell production of IFN‐γ was predictive of 90‐day mortality in AH patients 24 . Furthermore, IFN‐γ‐induced genes were significantly decreased in severe AH patients and these patients were highly susceptible to infections 29 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Soluble inflammatory mediators including interleukins have been implicated in ALD[ 60 , 89 , 90 ] and are associated with outcome in patients with AH[ 91 ]. Elevated serum IL-6 levels have recently been identified as a predictor of mortality in severe AH patients[ 64 ].…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%